Ravenous: how to get ourselves and our planet into shape - Dimbleby, Henry (London Profile Books, 2023)
Henry Dimbleby takes us behind the scenes to reveal the mechanisms that act together to shape the modern diet - and therefore the world. He explains not just why the food system is leading us into disaster, but what can be done about it.
Keywords: Environment -- Food Habits